2021
DOI: 10.1093/ehjci/jeab162
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the athlete’s heart: is myocardial work the new champion of systolic function?

Abstract: Aims We sought to investigate the correlation between speckle-tracking echocardiography (STE)-derived myocardial work (MW) and invasively measured contractility in a rat model of athlete's heart. We also assessed MW in elite athletes and explored its association with cardiopulmonary exercise test (CPET)-derived aerobic capacity. Methods and results Sixteen rats underwent a 12-week swim training program and were compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
0
20
3
1
Order By: Relevance
“…Jain et al (Sengupta et al, 2020) performed MW analysis in 24 half-marathon runners: all athletes had increase in LV volume and a mild reduction in peak GLS, associated with a normal value of GWI. While in a study of 20 elite swimmers, Tokodi et al showed that regular exercise training was associated with decreased GLS but increased values of GWI at rest (Tokodi et al, 2021). The inconsistency between the current study and previous research could be explained by the sensitivity of GWI to afterload and thus its wide range of normal values that overlaps with pathological ones (Manganaro et al, 2019).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Jain et al (Sengupta et al, 2020) performed MW analysis in 24 half-marathon runners: all athletes had increase in LV volume and a mild reduction in peak GLS, associated with a normal value of GWI. While in a study of 20 elite swimmers, Tokodi et al showed that regular exercise training was associated with decreased GLS but increased values of GWI at rest (Tokodi et al, 2021). The inconsistency between the current study and previous research could be explained by the sensitivity of GWI to afterload and thus its wide range of normal values that overlaps with pathological ones (Manganaro et al, 2019).…”
Section: Discussioncontrasting
confidence: 87%
“…A major finding of the current study is that GWI and GWE indexed by body mass correlate with relative VO 2 max in preadolescent athletes. Previous studies in adult athletes have reported the association between either GWI or GWE at rest and relative VO 2 max (Tokodi et al, 2021;D'Andrea et al, 2020). The current study is different in that the GWI and GWE alone did not demonstrate correlation with either VO 2 max or relative VO 2 max but the indexed ones did.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding of higher GWE in PACR is more evident after 6 months of HT since before 6 months, some degree of ischemic injury might be present in both groups ( 5 ) as a confounding factor for rejection injury. Interestingly, in an elegant study by Tokodi et al ( 20 ), GLS was impaired in elite swimmers, while indices of MW were completely normal, maintaining normal LV function, probably as a consequence of a better description of myocardial contractility. In summary, MW indices mighty precociously differentiate PACR compared to GLS in the first year of HT.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, GWE is significantly higher in PACR subjects than in NACR subjects, including 1-year HT and borderline HT, if only less than 6 months of HT are included. A possible hypothesis for this finding is that patients with PACR have increased afterload as a consequence of neurohormonal activation ( 3 ) and slightly higher blood pressure; to maintain normal ejection fraction, the contractile efficiency must be compensated ( 20 ). This finding of higher GWE in PACR is more evident after 6 months of HT since before 6 months, some degree of ischemic injury might be present in both groups ( 5 ) as a confounding factor for rejection injury.…”
Section: Discussionmentioning
confidence: 99%